2015
DOI: 10.1007/s13277-015-3883-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-224: as a potential target for miR-based therapy of cancer

Abstract: MicroRNAs (miRNAs) are small noncoding RNA molecules which regulate the target gene expression posttranscriptionally. Increasing studies have shown that microRNAs play important roles in multiple biological pathways. For instance, aberrant expression of microRNA-224 (miR-224) plays a vital role in tumor biology in various types of human cancer. Here, we aim to summarize the molecular mechanisms that lead to the overexpression of miR-224 in cancers, analyze the effect of miR-224 on tumor biology, and reveal the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
(74 reference statements)
0
17
1
1
Order By: Relevance
“…To the best of our knowledge, this was the first report that the relative levels of miR-224 in different types of breast cancer tissues were associated inversely with the aggressiveness of breast cancers. Although miR-224 has been shown to promote tumorigenesis of HCC, CRC and gastric cancers [79] our data suggest that miR-224 may inhibit the development and progression of breast cancers. Hence, our findings argue that miR-224 may have varying functions in regulating the development and progression of different types of cancers.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To the best of our knowledge, this was the first report that the relative levels of miR-224 in different types of breast cancer tissues were associated inversely with the aggressiveness of breast cancers. Although miR-224 has been shown to promote tumorigenesis of HCC, CRC and gastric cancers [79] our data suggest that miR-224 may inhibit the development and progression of breast cancers. Hence, our findings argue that miR-224 may have varying functions in regulating the development and progression of different types of cancers.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that miR-224 can bind to the tumor suppressors of TNFα-induced protein 1 (TNFAIP1) and Smad4, Raf kinase inhibitor protein (RKIP), apoptosis inhibitor-5 (API-5), PH domain leucine-rich-repeat protein phosphatase 1 (PHLPP1), and PHLPP2 to promote the survival and proliferation of colorectal cancer (CRC) and hepatocellular carcinoma (HCC), but bind to the TRIB1 to promote apoptosis of prostatic cancer cells [711]. Furthermore, miR224 binds to the Smad4 and Homeobox D10 (HOXD10) to promote migration of HCC and CRC [8, 12] while it binds to the TPD52 to inhibit migration of prostatic cancer PCa cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…A previous review reported by Chen et al [45] demonstrated that miR-224 may be a potential therapeutic target for malignant tumors via targeting associated genes and pathways. In our study, we conducted a meta-analysis including 16 studies from the literature and two studies from microarrays to quantitatively estimate the prognostic capability of miR-224-5p.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule is also reported as a master regulator of cell cycle progression and its overexpression results in G1/S checkpoint release followed by accelerated cell growth [62]. Recent studies have shown that miR-224 is more highly expressed in not only HCC but also esophageal cancer, non-small cell lung cancer, colorectal cancer, cervical cancer and glioma, and this molecule has a proliferative effect on these cancer cells through direct interactions with various tumor-suppressor genes, such as CAMKK2, ADAM17, Homeobox D 10 and RKIP [63][64][65][66][67][68]. Moreover, the clinical relevance of miR-224 had been reported as an indicator of chemoresistance to cisplatin, methotrexate and R-CHOP, radiation sensitivity and a prognostic factor of sorafenib-treated patients [69][70][71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%